2019
DOI: 10.1002/jso.25765
|View full text |Cite
|
Sign up to set email alerts
|

Mechanotechnical faults and particular issues of anastomotic complications following robot‐assisted anterior resection in 968 rectal cancer patients

Abstract: Background As most risk factors for anastomotic complications (AC) in rectal cancer patients appear to be noncorrectable, it is needed to find the correctable causes. Additionally, the outcomes of indocyanine‐green fluorescence imaging (IFI) and robot‐stapled anastomosis have yet been undetermined. Methods This study retrospectively analyzed 968 consecutive patients with rectal cancer, who underwent curative robot‐assisted anterior resections between 2010 and 2018. IFI parameters and stapling features in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…These two parameters may explain our findings of non‐reducing anastomotic complication through IFI. Most technical errors are due to multiple linear stapling and uneven depth of stapling, as previously reported 22,23 . Anatomical defects included restrictive pelvis, bowel adhesion, and malrotation/short mesocolon.…”
Section: Discussionmentioning
confidence: 58%
“…These two parameters may explain our findings of non‐reducing anastomotic complication through IFI. Most technical errors are due to multiple linear stapling and uneven depth of stapling, as previously reported 22,23 . Anatomical defects included restrictive pelvis, bowel adhesion, and malrotation/short mesocolon.…”
Section: Discussionmentioning
confidence: 58%
“…Furthermore, factors such as the ligation site of IMA have also been studied; studies found that low ligation may result in a reduced rate of AS following colorectal cancer surgeries and then suggest that low ligation should be preferred over high ligation [22,29]. Another factor is blood perfusion evaluated using ICG, which signi cantly reduces AL and AS rates [30]. However, none of these factors thought to in uence AS was identi ed as meaningful in this study.…”
Section: Discussionmentioning
confidence: 87%
“…Intraoperative risk factors include the inability to achieve a tension-free anastomosis and poor blood supply to the ends of bowel used for anastomosis, blood loss and blood transfusions, prolonged operating time, and intraoperative contamination [10][11][12][13][14][15][16]. Using multiple stapler firings across the rectum, which is commonly done in laparoscopic and robotic approaches, may also be associated with a higher risk for anastomotic leak [21][22][23]. The operating surgeon is another potential risk factor, although little is known about which surgeon characteristics would increase the risk for a surgical complication [24,25].…”
Section: Risk Factorsmentioning
confidence: 99%